Walt disney's lady and the tramp (Grolier Books Danbury, Connecticut, 1994)
Lady has a happy life but The Tramp, a homeless dog, tells her that will change when a baby comes into the house. And when a baby does come, Lady worries. Darling and Jim Dear have less time for her and then, to make matters worse, Aunt Sarah comes and immediately orders Lady to be tied up in the yard... and muzzled! The Tramp releases her from her rope and her muzzle and offers to go anywhere she likes; he's shocked when she chooses home. Thankfully, they arrive in time to alert the family to a fire and, out of gratitude, Jim Dear and Darling take The Tramp into their home. Anna Ligtenberg, Amazon reviewer